Feeding chicory silage, but not Se-yeast or a single injection of inorganic Se, affects metabolism, fat in milk, and type I immunity in transition ewes - Ford, Hunter; Hasan, Daniella; Ates, Serkan; Puerto-Hernandez, Gracia; Klopfenstein, Joseph J.; Trevisi, Erminio; Smallman, Mary; Matra, Maharach; Bionaz, Massimo (Frontiers in Animal Science, 2024)
In the study, we assessed the effect on performance and health of a single injection of inorganic Se prepartum or feeding chicory silage and organic Se supplementation during the peripartum in ewes. Approximately one month before lambing, 45 pregnant Polypay ewes were moved into single pens and randomly assigned to 5 groups to be fed either grass or chicory silage and supplemented or not with 3.6 mg Se/day as selenium yeast or given a single prepartum injection of Na-selenite. Daily dry matter intake (DMI), water intake, milk production and components, blood metabolic, immune and inflammatory parameters, and blood micromineral levels were measured. DMI was lower in ewes fed chicory silage, although no statistical differences in milk yield were observed. Very few differences were observed in milk components, except fat %, which was higher among ewes fed chicory silage. The type of silage had a significant effect on the fatty acid profile of the milk, with the milk from ewes fed chicory having a higher proportion of unsaturated fatty acids and overall improved health indices compared to the milk from ewes fed grass silage. Blood NEFA and BHBA were higher in ewes fed chicory vs. grass silage. Neither silage type nor Se supplementation had a strong effect on most of the parameters associated with immune or inflammatory function, except for the liver enzymes GGT and GOT, which were lower, and a larger type I/type II ratio immune response measured by the DxD2 assay among ewes fed chicory vs. grass silage. No effects on parasite fecal egg counts were observed. Supplementation of ewes with Se-yeast resulted in higher blood levels of Se, whereas the one-time prepartum injection had no significant effect on whole blood Se levels. Feeding chicory silage and supplementing Se during the transition period had a minimal impact on ewe performance and health.